2017
DOI: 10.1007/s10980-017-0556-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of bumblebees, heteropteran bugs and grasshoppers maintained by both: abandonment and extensive management of mountain meadows in three regions across the Austrian and Swiss Alps

Abstract: Context Abandonment of extensively managed meadows is an ongoing global challenge in recent decades, particularly in mountain regions, and directly affects plant diversity. However, the extent to which plant diversity further affects associated insect pollinators or herbivores is little investigated. Objectives We focused on the effects of abandonment of mountain meadows on species richness and assemblages of bumblebees, bugs and grasshoppers. Specifically, we investigated the influence of vegetation cover, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
4
29
1
Order By: Relevance
“…Abandonment had a negative effect on plant richness, which will decrease syrphid abundance. Our results also supports previous observation that declines in plant species cause a decline of pollinators (Walcher et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Abandonment had a negative effect on plant richness, which will decrease syrphid abundance. Our results also supports previous observation that declines in plant species cause a decline of pollinators (Walcher et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…In European mountains, there is a trend of abandonment in formerly managed meadows (Prévosto et al., ). Managed semidry grassland has often been observed species rich (Walcher et al.,). Thus, such grassland harbor rich natural values (Kampmann, Lüscher, Konold, & Herzog, ) which is one of the attractions for eco‐tourists (Stöcklin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants perceived the abandoned meadow as having greater biodiversity than the managed one. Whether this is correct is difficult to confirm, but research on flora and fauna biodiversity in Alpine mountain meadows has often observed higher plant biodiversity in extensively managed meadows (Boschi & Baur 2008;Tocco et al 2013;Tasser & Tappeiner 2002), even for that part of the BR (Walcher et al 2017), while results for fauna biodiversity varied between meadow types (Ranta & Vepsäläinen 1981). In addition, the managed meadow of this study had recently been cut and flowering plants were very rare, making it difficult for participants to recognize the plant biodiversity.…”
Section: Perceived Health Effectsmentioning
confidence: 99%
“…In light of the two hypotheses, we may explain the variation in the correlation between plant–insect species richness among previous studies. First, most previous studies have attempted to explain insect species richness by total plant species richness rather than by utilized plant species richness, and some of them have found no significant relationships between them (Vessby et al 2002; Axmacher et al 2009; Walcher et al 2017). On the contrary, a study on plant and their associated insect species (collected from individuals of the focal plants) showed a significant relationship between their species richness even accounting for geographic and environmental variables (Kemp and Ellis 2017).…”
Section: Discussionmentioning
confidence: 99%